Anthropocentric phraseological units of the Tatar language - Raushaniya S. Nurmukhametova, Firuza R. Sibgaeva,; Smagulova, Guldarkhan N. (Opción, 2019)
The article is devoted to the analysis of some phraseological units with the evaluative component of a person (by the material of the Tatar language) via the method of statistical data analysis, the method of seminal analysis, the method of full component analysis, the method of etymological analysis. As a result of the semantic analysis of the studied units, the description of a person consists of a set of positive, negative and neutral features. In conclusion, the phraseological composition of a language is a national phenomenon and its source is the speech of a native speaker